Ultra regular covering space and its automorphism group - Han, Sang-Eon (Zielona Góra: Uniwersytet Zielonogórski)
In order to classify digital spaces in terms of digital-homotopic theoretical tools, a recent paper by Han (2006b) (see also the works of Boxer and Karaca (2008) as well as Han (2007b)) established the notion of regular covering space from the viewpoint of digital covering theory and studied an automorphism group (or Deck?s discrete transformation group) of a digital covering
Keywords: digital image; digital isomorphism; (ultra) regular covering space; digital covering space; simply k-connected; Deck?s discrete transformation group; compatible adjacency; digital wedge; automorphism group